Contributions to the comparative anatomy of the nasal capsule and the organ of Jacobson of the Lacertilia - Malan, M. E. (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1945.